The Effects of Selected Microbial Inoculum on Microbial and Biochemical Changes During Cocoa Fermentation - Setyohadi, (1990)
Fermentation and drying play an important role in influencing the overall quality offermented cocoa beans . A study was conducted to look into the effect of various micr obialinocula (Sacchar omyce scerevisiae,Hansenulaa nomala and Acetobacteraceti indifferent combination) on change sin mass temperature, pH, ethanol, ethylacetate, lactic and acetic acid contents and the degree offer mentation index (FI) of cocoa beans fermented over a period of six days. The d riedtreated cocoa beans we real so analysed for pH,titra table acidity , lactic and acetic acids, ethylacetate content and fermentation index. The temperature of bean mass inoculated with microbialinoculum was found to increase to a maximum ranging from 47 to 48°C. The pH of cocoa cotyledon was found to decrease from pH 6.8 to 5.0 - 5.3,while the fermentation index (F.r.) of fermented beans was found to increase from 0.56 to 1.44. Beans inoculated wit h yeasts (cerevisia e+g. anomala) were found to yield higher ethyl acetate (0.5639 g/100g) and lower levels of acetic and lactic acids (0.0748g /100g and 0.0443 g/100 g,respectively) as compared to the controlled sample at the end of 6 days. The control led bean sample was found to have 0.2436g /100g ethyl acetate and 0.1669g /100g, 0.2565g/100 g of acetic and lactic acid content, respectively after a 6 day fermentation period.